Feline fatale [large type] - Brown, Rita Mae; Brown, Sneaky Pie, 1982- (Brown, Rita Mae. Mrs. Murphy mystery, 2024)
Death stalks the Blue Ridge Mountains once again and Mary Minor "Harry" Harristeen, along with her beloved cats and dogs, is on the case.